Meningkatkan Hasil Belajar Matematika Menggunakan Model PBL Kombinasi Dengan Pendidikan Matematika Realistik Indonesia dan NHT - Aulianti Aulianti; Khairil Anwar (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
The problem that occurs in this study is the low learning outcomes caused by a lack of teachers in using models and media in learning. Alternatives to solving these problems are using the Problem Based Learning model, Indonesian Realistic Mathematics Education, and Number Head Together. The research objective is to describe the activities of educators, students, and to analyze learning outcomes. The approach used in this discovery is a qualitative approach with the type of PTK, which is carried out in 2 cycles consisting of three meetings. The subjects of this study were 18 grade VI students at SDN Kelayan Selatan 10. Qualitative data obtained through observing the activities of educators and students. While quantitative data through measurement techniques with individual written tests. Data analysis in this finding uses descriptive analysis techniques and cross-tabulations translated into tables, graphs and interpretations with percentages. The results of these findings show that educator activities get a score of 24 in the "very good" category. experienced an increase from a score of 30 to 36 in the "Very Good" category. Classical student activities reached 100% in the "very active" category. As well as student learning outcomes have achieved 100% completeness classically and individually. Based on these findings it can be concluded that using the PBL, PMRI, and NHT models can increase learning activities and outcomes.